Evidence of Paraoxonases 1, 2, and 3 Expression in Human Ovarian Granulosa Cells - Irantzu Pérez-Ruiz; José-Ignacio Ruiz-Sanz; María-Luisa Hérnandez; Rosaura Navarro; Marcos Ferrando; Zaloa Larreategui; María-Begoña Ruiz-Larrea (Antioxidants, 2021)
Increasing evidence suggests that the antioxidant paraoxonase proteins, PON1, PON2, and PON3, have a role in reproduction and may be synthesized by ovarian cells. The aim of this work was to investigate whether human ovarian granulosa cells (GC) express paraoxonases 1, 2, and 3 (PON1, PON2, and PON3) at both the transcriptional and protein levels. Cells were purified from follicle samples of women undergoing ovarian stimulation at oocyte retrieval. We analyzed mRNA by polymerase chain reaction using specific primers for the different variants and quantified the proteins by Western blot using commercially available human recombinant PON proteins as standards. The protein subcellular distribution was determined by immunofluorescence and confocal microscopy and the cell cycles by flow cytometry. Thymidine was used for cellular synchronization at G1/S. Human hepatoma HepG2 and immortalized granulosa COV434 cell lines were used to optimize methodologies. mRNAs from PON1, the two variants of PON2, and PON3 were detected in GC. The cells actively secreted PON1 and PON3, as evidenced by the protein detection in the incubation medium. PON1 and PON3 were mainly distributed in the cytoplasm and notably in the nucleus, while PON2 colocalized with mitochondria. Subcellular nucleo-cytoplasmic distribution of PON1 was associated with the cell cycle. This is the first evidence describing the presence of mRNAs and proteins of the three members of the PON family in human ovarian GC. This study provides the basis of further research to understand the role of these proteins in GC, which will contribute to a better understanding of the reproduction process.